Efek Mulsa Jerami Padi dan Pupuk Kandang Sapi terhadap Pertumbuhan dan Hasil Bawang Merah di Daerah Pesisir - MAYUN, IDA AYU (AGRITROP, 2007)
The objective of this experiment was to study the effect of mulching and organic fertilizer on growth and yieldof shallot (Allium ascalonicum L.) in coastal seaboard. The experiment was arranged in Randomized CompletelyBlock Design (RCBD) with two treatments. First factor are mulching with two levels: without mulch (M0) and withmulch (M1). Second factor are dosages of organic fertilizer: without fertilizer (P0), 10 T Ha-1 fertilizer (P1), 20 THa-1 fertilizer (P2), 30 T Ha-1 fertilizer (P3), 40 T Ha-1 fertilizer (P4), and 50 T Ha-1 fertilizer (P5). The experimenttreatment was arranged by three replications. The data were analysis by variance and LSD analysis, correlationanalysis, and regression analysis. The results showed that the interaction effects of the mulching and organic fertilizeron growth and yield of shallot were significantly different , except on the 10 T Ha-1 (P1) to 30 T Ha-1 fertilizer(P3) the treatment was no effect on total leafs per hill in without mulch (M0). The highest yield of bulb was 7.78Q Ha-1 without mulch (M0) and 12.27 Q Ha-1 with mulch (M1). The effect of mulching was increase the yield was35.13 %.